Otolaryngology-related symptoms of COVID-19 in children in the post-epidemic era: a cross-sectional web-based survey study - Chen, Yong-chao; Wang, Xin; Teng, Yi-shu; Jia, De-sheng; Li, Lan; Pan, Hong-guang (Frontiers in Pediatrics, 2023)
Purpose China adjusted and optimized its prevention and control strategies in December 2022, and China entered a new era of the coronavirus epidemic. Here, we describe the general and otolaryngology-related symptoms of COVID-19 in children during the first pandemic in the post-epidemic era, focusing on the frequency and severity of smell and taste loss, as well as the recovery process and its influencing factors. Methods From January 2 to 7, 2023, we conducted a cross-sectional online questionnaire survey through Questionnaire Stars in order to collect relevant information about COVID-19 of children in Shenzhen. Results A total of 1247 valid questionnaires were received, with an effective response rate of 78.72%. All of the diagnoses were confirmed by nucleic acid or antigen test for COVID-19. Among the subjects, the sex ratio of male to female was more inclined to male (1.35：1), the age was 3 to 16 years old, with an average of 10.13 ±2.82 years old. The most common symptoms were cough (58.24%), stuffy nose (56.18%), headache (42.09%), fatigue (40.44%) and sore throat (31.63%). 6.43% of the children reported dysosmia, the mean time of the duration of dysosmia was 5.38±2.92 days, the mean score of the severity of the dysosmia as assessed by visual analogue scale (VAS) was 4.63±2.29. 13.34% reported dysgeusia, the mean time of the duration of dysgeusia was 4.77±3.98 days, the mean score of the severity of the dysgeusia as assessed by VAS was 5.12±2.29. Univariate and multivariate logistics regression analysis showed that the prevalence of taste and olfactory disorders increased with age, mainly in children with severe symptoms and older children. Conclusion In the post-epidemic era, due to the weakening of the pathogenicity of the subvariant of Omicron, the overall condition of children with COVID-19 was mild, the incidence of olfactory and taste disorders was low, the recovery was faster, and the prognosis was better. In our study, cough, runny nose and sore throat were the most common symptoms, and the prevalence of taste and olfactory disorders increased with age, mainly in older children with severe symptoms.